352 A Retrospective Audit to Determine the Appropriateness of Antibiotic Use in Surgical Patients in MKUH. (4th May 2021) - Stone, H; Khanna, A; Keeler, B
Abstract: Introduction: This audit's aim is to determine the appropriateness of antibiotics dispensed in Emergency Surgery Clinic (ESC) for a two-month period in 2020. Antibiotic stewardship promotes appropriate antibiotic use in clinical settings whilst limiting unnecessary use. Appropriate antibiotic use is important in reducing the risk of antibiotic resistance. Method: We extracted the following details from 801 patients' electronic notes who attended MKUH ESC: diagnosis, prescription of antibiotics, hospital admission, and re-attendance at the ESC. Prescriptions were analysed as to whether they were in accordance with our microbiology guidelines. Patients were analysed as a collective and within diagnosis sub-specialities (appendicitis, wound infection, gallstones/cholecystitis, testicular pathology, UTI, diverticulitis, renal stones and abscesses). Results: 218 (27%) patients were given antibiotics, 180 (22%) patients re-attended ESC and 111 (14%) were admitted. Only 77 patients (35%) receiving antibiotics were prescribed appropriately. Outcomes also varied by diagnosis. All patients presenting with UTI (n = 15) were treated correctly. In contrast, only 71% of patients with renal stones (n = 68) were incorrectly treated with antibiotics. Conclusions: Two-thirds of patients receiving antibiotics were inappropriately prescribed. This together with the variation by diagnosis would suggest further measures be introduced to support antibiotic stewardship and mitigate the risk of antibiotic resistance.